Curriculum Design For Non-Formal Diniyah Madrasah at Islamic Boarding School - Halid, Ahmad; bin Jali, Hasan (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This study focuses on a very interesting study of "Non-formal Early Childhood Education Curriculum (MDNF) Planning in Islamic Boarding Schools. Non-formal early childhood education is organized based on the recognition of excellent educational practices and takes place in Islamic boarding schools in order to develop the potential of students to become human beings who believe and fear Allah SWT, have noble morals, are knowledgeable, capable, creative, independent, and become democratic and responsible citizens. This study is discussed using a descriptive qualitative method. The problem is how is the planning of the Non-formal Early Childhood Education Curriculum (MDNF) at the Miftahul Ulum Wirowongso Ajung Jember Islamic Boarding School? The aim is to develop the planning of the Non-formal Early Childhood Education Curriculum (MDNF) at the Miftahul Ulum Wirowongso Ajung Jember Islamic Boarding School? The PDNF curriculum design theory uses the results of the theories of Beane, J.A, Olivia.P, F, Stoner, J.A.F and Terry, R, G. The results of this study are (1) Planning based on the vision, mission to achieve Tafaqquh Fiddin (2) MDNF Pesantren Miftahul Ulum Based on community demands (adaptability), (3) PDNF Curriculum Design: Provides freedom to Madrasahs in developing education and learning (4) MDNF Curriculum Design: Provides freedom to develop study books as an expansion of insight and support for subjects in MDNF. (5) Implementation of the Madrasah program or non-formal diniyah education (MDNF) in the morning is carried out by formal education units at the Elementary Madrasah, Junior High Madrasah, and Vocational High School level.